Suspended Sediment and Turbidity Relationships for Individual and Multiple Catchments - Sulaiman, Wan Nor Azmin; Hamid, Mohamad Rosnani (Universiti Putra Malaysia Press, 1997)
The relationships between suspended sediment concentrations and turbidity were analysed at rising and falling stages, using individual and combined catchments. Results suggested a high correlation exists between suspended sediment concentration and turbidity for most of the field data. The least square fit of all the data suggested that the relationships obtained followed a power function in the form of Y = a(T)b. Consistent turbidity and suspended sediment concentration relationships found in this study imply that turbidity measurement could reasonably be used as a surrogate in estimating stream suspended sediment concentration of the study catchments and of those under similar conditions.